Peran Dinas Pengendalian Penduduk Keluarga Berencana Pemberdayaan Perempuan Dan Perlindungan Anak Dalam Menangani Perundungan Terhaadap Anak Di Kabupaten Ciamis (Studi Kasus Di Kecamatan Banjarsari) - Ayu Yuliani; Dini Yuliani; Asep Nurdin RA (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This research is motivated by the increasing number of cases of violence against children in Ciamis Regency, there have been 47 cases of violence against children recorded until September 2024, this number exceeds the total number of cases throughout 2023 which only reached 38 cases, one indicator of the increase in cases of violence against children is the lack of education and social support in handling cases of violence. The institution responsible for handling cases of violence against children is the Department of Population Control, Family Planning, Women’s Empowerment and Child Protection of Ciamis Regency. In this study, researchers used qualitative research methods with data analysis, observation and interviews using the theory of Prof. Dr. Sondang P Siagian (2020: 142). This study aims to determine the role and efforts of the Department of Population Control, Family Planning, Women’s Empowerment and Child Protection in handling bullying against children in Ciamis Regency. Based on the results of the research that has been conducted, the Department of Population Control, Family Planning, Women’s Empowerment and Child Protection of Ciamis Regency in Handling Bullying Against Children (Case Study in Banjarsari District) is not optimal, it is proven that cases of violence or bullying against children still occur and there are still many cases of violence or bullying against children that are not handled.